High-adhesion and high-flexibility UV coating for plastic titanium glasses frame and preparation method of high-adhesion and high-flexibility UV coating
By using raw materials such as multifunctional polyurethane acrylate, polyester acrylate and functional acrylate monomers, high adhesion and high flexibility UV coatings are prepared, which solves the adhesion and flexibility of existing coatings on TR90 glasses frames. The problem of undesirable achieves better wear resistance and curing speed.
Patent Information
- Application Number
- CN202411372177.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-18
AI Technical Summary
The existing UV coatings have poor adhesion and flexibility on the TR90 glasses frame, which are prone to cracking and falling off, and cannot fully meet market demand.
High adhesion and high flexibility UV coatings are prepared by dispersing and stirring through a high-speed disperser.
It significantly improves the adhesion and flexibility of UV coating on the TR90 glasses frame, enhances the wear resistance and curing speed of the coating, and meets the use needs of the TR90 glasses frame.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0005067863180000041
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a high-adhesion and high-flexibility UV coating for a plastic titanium eyeglass frame and a preparation method thereof. Background Art
[0002] In the eyeglass frame industry, the mainstream eyeglass frame materials on the market include metal, alloy, carbon fiber, plastic or resin materials. Metal materials are expensive, and alloy materials are prone to corrosion and rust. The most widely used eyeglass frame material is plastic titanium (TR90), which is a polymer material with memory function, light weight, super toughness and impact resistance, which can effectively prevent the frame from breaking and reduce the damage to the eyes and face caused by frame breakage during exercise. In addition, TR90 material also has the characteristics of high temperature resistance, chemical resistance, bright and beautiful colors, and excellent safety.
[0003] UV curing plastic coating is an ideal plastic surface protective layer material. The light curing process used is pollution-free, fast curing speed and high production efficiency. UV curing plastic coating is cured at room temperature, very suitable for plastic workpieces, does not produce thermal deformation, and the cross-linking density after curing is much higher than that of hot baking type coatings, so the coating has good performance in hardness, wear resistance, acid and alkali resistance, etc.
[0004] The surface energy of plastic is lower than that of ordinary metal materials. When choosing a suitable coating for plastic products, it is necessary to consider the surface properties of the coating material, the interface characteristics between the coating and the plastic, and the characteristics of the plastic itself.
[0005] CN201811630896 discloses a UV / moisture dual-curing eyeglass frame coating and a preparation method thereof. The eyeglass frame coating prepared by the method can be quickly cured under a UV-LED light source, and the surface is dry to reach a certain hardness and strength; after being placed in the air for 12 hours, it is completely cured, and the coating is solvent-free, which solves the problem that the solvent content of the coating currently used for the eyeglass frame is high and the curing speed is slow. The eyeglass frame material used in this method is a PC eyeglass frame. The PC material has high hardness and poor toughness compared with the TR90 material. The temples are often bent during daily use. The coating cannot fully meet the problems of adhesion and flexibility, and the coating is prone to cracking and falling off. Therefore, it cannot be used as a UV coating for TR90 material.
[0006] CN96118331 discloses a UV curing coating for plastic products, which is prepared by using chlorine-modified acrylic epoxy, nitrogen-modified acrylic polyurethane, chlorine-modified trimethylolpropane triethylene ester, nitrogen-modified 2-ethoxy acrylate, ferrocene-modified benzophenone, tertiary amine salt of acrylic acid, polyacrylate and silicone as raw materials according to a certain weight composition, mainly to solve the problem of poor adhesion to plastic products such as PE and PVC. The adhesion and flexibility of TR90 material are also not ideal. In addition, the prepolymer and diluent selected in this method are chlorine-modified, which cannot meet the current environmental protection requirements of low halogen.
[0007] In summary, the existing UV coating process and technology need to improve the adhesion, flexibility and abrasion resistance of the existing UV coating to achieve the use effect on the TR90 eyeglass frame. Summary of the invention
[0008] Purpose of the invention: The present invention adopts raw materials readily available in the market to produce a UV coating with simple and efficient process, which has excellent adhesion and flexibility to the TR90 eyeglass frame substrate.
[0009] Technical solution: In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0010] A high-adhesion, high-flexibility UV coating for a plastic titanium (TR90) eyeglass frame and a preparation method thereof, comprising one or more of the following quality raw materials:
[0011] Multifunctional polyurethane acrylate, polyester acrylate, acrylate monomer, photoinitiator, leveling agent, defoamer, drying agent.
[0012] As a preferred solution, the high-adhesion and high-flexibility UV coating for TR90 eyeglass frames described above is made of the following raw materials in percentage by mass:
[0013] 24-38% of multifunctional polyurethane acrylate, 25-35% of polyester acrylate, 22-30% of acrylate monomer, 1-5% of photoinitiator, 0.2-0.5% of polyacrylate leveling agent, 0.2-0.5% of silicone defoamer, and 0.2-0.5% of drying agent.
[0014] As a preferred embodiment, the multifunctional polyurethane acrylate is at least one of aliphatic polyurethane diacrylate, aliphatic polyurethane triacrylate, aliphatic polyurethane hexaacrylate, aliphatic polyurethane nonaacrylate, or a mixture thereof.
[0015] As a preferred embodiment, in the above-mentioned high-adhesion and high-flexibility UV coating for plastic titanium eyeglass frames, the acrylate monomer is at least one of ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, di-trimethylolpropane tetraacrylate (DiTMP4A), neopentyl glycol diacrylate (NPGDA), polyethylene glycol dimethacrylate, cyclotrimethylolpropane formal acrylate (CTFA) or a mixture thereof. These acrylate monomers are all functional monomers, which can be used as active diluents for UV radiation crosslinking, and can also become a crosslinking polymer component to improve the adhesion and flexibility of the coating.
[0016] As a preferred embodiment, the high-adhesion, high-flexibility UV coating for the plastic titanium eyeglass frame described above, the polyester acrylate is at least one of monofunctional polyester acrylate, multifunctional polyester acrylate, hyperbranched polyester acrylate, modified polyester acrylate or a mixture thereof.
[0017] As a preferred embodiment, in the above-mentioned high-adhesion, high-flexibility UV coating for plastic titanium eyeglass frames, the initiator is at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexyl-phenyl ketone, benzophenone, and 2,4,6-trimethylbenzoyldiphenylphosphine oxide, or a mixture thereof.
[0018] As a preferred embodiment, in the above-mentioned high-adhesion and high-flexibility UV coating for plastic titanium eyeglass frames, the leveling agent is one or a mixture of an organic silicon leveling agent, a fluorocarbon leveling agent, and a polyacrylate leveling agent.
[0019] As a preferred embodiment, in the above-mentioned high-adhesion and high-flexibility UV coating for TR90 eyeglass frames, the defoaming agent is a silicone flow defoaming agent.
[0020] As a preferred embodiment, in the above-mentioned high-adhesion and high-flexibility UV coating for TR90 eyeglass frames, the drying agent is a cobalt drying agent.
[0021] The high-adhesion and high-flexibility UV coating for TR90 eyeglass frames described in the present invention is characterized by comprising the following steps:
[0022] 1) Add multifunctional polyurethane acrylate and polyester acrylate into a mixing tank according to mass percentage, and disperse them in a high-speed disperser at a speed of 1500 rpm for 10 minutes;
[0023] 2) Add DiTMP4A, NPGDA, CTFA and photoinitiator according to weight to the mixed materials in step 1 under low speed stirring at 200 rpm and disperse in a high-speed disperser at a speed of 1500 rpm for 20-30 minutes;
[0024] 3) The above-mentioned weight of leveling agent, defoaming agent, drying agent and the material mixed in step 2 are dispersed in a high-speed disperser at a speed of 1500 rpm for 20-30 minutes to obtain a UV coating for TR90 eyeglass frames.
[0025] The present invention mainly improves the defects and deficiencies of the existing UV coating on the TR90 eyeglass frame in terms of adhesion and flexibility through the following solutions:
[0026] 1. The present invention adopts multifunctional polyurethane acrylate and selects high-functionality aliphatic polyurethane hexaacrylate and aliphatic polyurethane nonaacrylate, so that the viscosity of the prepolymer increases during the crosslinking process and the crosslinking density is high.
[0027] 2. The present invention uses di-trimethylolpropane tetraacrylate (DiTMP4A), neopentyl glycol diacrylate (NPGDA), and cyclotrimethylolpropane formal acrylate (CTFA). These acrylate monomers are multifunctional monomers and can be used as active diluents for UV radiation crosslinking. They can also become components of crosslinking polymerization, increase the viscosity of the coating, and give the coating good adhesion, flexibility and curing speed.
[0028] 3. The polyester acrylate resin added in the present invention is a monofunctional polyester acrylate with low viscosity and low acid value. The free radicals or ionic segments can react with the unsaturated double bonds in the polyester acrylate molecules to continuously extend the segments and gradually increase the molecular weight, which can further improve the adhesion and flexibility of the coating.
[0029] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0030] By using raw materials that are easily available in the market and adopting a simple and efficient production process, a UV coating with excellent adhesion and flexibility is obtained, which is beneficial to improving the adhesion and flexibility of the TR90 eyeglass frame substrate. Specific embodiments
[0031] The embodiments of the present invention are described in detail below with reference to the examples. If no specific conditions are specified in the examples, the reaction is carried out according to conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0032] The present invention will be further described below in conjunction with the embodiments.
[0033] Example 1
[0034] 1. Resin coatings of different components are obtained by mixing the components in Table 1 below. The multifunctional polyurethane acrylate in the following embodiments is aliphatic polyurethane hexaacrylate SM6330 and aliphatic polyurethane nonaacrylate SM6901 produced by Jiangsu Sanmu Chemical Co., Ltd.; the polyester acrylate is a monofunctional polyester acrylate SM6407 produced by Jiangsu Sanmu Chemical Co., Ltd.; the photoinitiator is a mixture of 2-hydroxy-2-methyl-1-phenyl-1-propanone and benzophenone in a mass ratio of 2:1; the acrylate monomer is a mixture of di-trimethylolpropane tetraacrylate (DiTMP4A), neopentyl glycol diacrylate (NPGDA), and cyclotrimethylolpropane formal acrylate (CTFA) produced by Jiangsu Sanmu Chemical Co., Ltd.; the leveling agent is a polyacrylate leveling agent; the defoaming agent is a silicone defoaming agent; and the drying agent is VOK-Cobalt 12 cobalt drying agent produced by Volker, Germany.
[0035] Table 1 Raw material composition of each embodiment
[0036]
[0037] The above different formula resin coatings are prepared according to the following steps:
[0038] 1) Add multifunctional polyurethane acrylate and polyester acrylate into a mixing tank according to mass percentage, and disperse them in a high-speed disperser at a speed of 1500 rpm for 10 minutes;
[0039] 2) Add DiTMP4A, NPGDA, CTFA and photoinitiator according to weight to the mixed materials in step 1 under low speed stirring at 200 rpm and disperse in a high-speed disperser at a speed of 1500 rpm for 20-30 minutes;
[0040] 3) The above-mentioned weight of leveling agent, defoaming agent, drying agent and the material mixed in step 2 are dispersed in a high-speed disperser at a speed of 1500 rpm for 20-30 minutes to obtain a UV coating for TR90 eyeglass frames.
[0041] 2. Performance Testing
[0042] The UV coating prepared in Example 1 to Example 11 was sprayed on a TR90 plate using a W71 Iwata spray gun and then cured by a UV mercury lamp with a light intensity of 500 mj / cm2 to obtain an organic coating with high adhesion and high flexibility of less than 10 um. The performance test indicators are shown in Table 2.
[0043] Table 2 Panel and paint film performance test results
[0044]
[0045]
[0046] Among them, the hardness test adopts the pencil method, and the reference standard is GB / T6739-2006;
[0047] The fineness test uses a scraper fineness meter to measure the fineness, and the reference standard is GB / T1724-2019;
[0048] The adhesion test adopts the hundred-grid method, and the reference standard is GB / T 9286-1998, among which grade 0 is the best;
[0049] The flexibility test adopts the standard GB / T1731-93 "Paint film flexibility test method" to test the flexibility of the paint film using a flexibility tester;
[0050] For the wear resistance test, an abrasion tester is used with a special sandy rubber (rubber model: LER902K). A load of 500G is applied, and the sample surface is rubbed back and forth for 500 cycles at a speed of 40-60 times / minute and a stroke of about 20mm to observe whether the paint film has surface gloss loss, bottom exposure, or shedding.
[0051] The curing speed is determined by using a Biaugeda 8213 UV curing machine, and the UV lamp power is 100W / cm.
[0052] The test results in Table 2 above show that the other components of formulas 1 to 3 and 4 to 6% are the same, only the mass ratios of DiTMP4A, NPGDA and CTFA are different, and the wear resistance of the paint film is different, among which 1:2:1 is the best. In addition, by screening different proportions of aliphatic polyurethane hexaacrylate SM6330 and aliphatic polyurethane nine acrylate SM6901, the results show that the UV coating prepared by formula 10 has better adhesion and flexibility and good wear resistance on the TR90 eyeglass frame, and has broad market application prospects. It also shows that the coating properties prepared by polyurethane acrylate and polyester acrylate in different dosage ratios have great differences. Polyurethane acrylate is a multifunctional polyurethane acrylate. Its carbamate bonds give the material high wear resistance. These bonds can form multiple hydrogen bonds between polymer chains, increasing the interaction between molecules and making the material surface harder and more wear-resistant. Polyester acrylate resin uses monofunctional polyester acrylate with low viscosity and low acid value. Free radicals or ionic segments can react with unsaturated double bonds in polyester acrylate molecules to continuously extend the segments and gradually increase the molecular weight, which can further improve the adhesion and flexibility of the coating. When the high-functionality acrylate monomers di-trimethylolpropane tetraacrylate (DiTMP4A), neopentyl glycol diacrylate (NPGDA), and cyclotrimethylolpropane formal acrylate (CTFA) are in a mass ratio of 1:2:1, they contain multiple groups that can participate in the curing reaction. These groups can react quickly under ultraviolet irradiation, thereby accelerating the curing speed of the coating. In addition, they can form a denser cross-linked network structure. Therefore, the cured coating usually has higher hardness, adhesion and flexibility.
[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-adhesion, high-flexibility UV coating for plastic titanium eyeglass frames, characterized in that: It is made of the following raw materials in percentage by mass: 24-38% of multifunctional polyurethane acrylate, 25-35% of polyester acrylate, 22-30% of acrylate monomer, 1-5% of photoinitiator, 0.2-0.5% of polyacrylate leveling agent, 0.2-0.5% of silicone defoamer, and 0.2-0.5% of drying agent.
2. The high-adhesion and high-flexibility UV coating for plastic titanium eyeglass frames according to claim 1, characterized in that: The multifunctional polyurethane acrylate is at least one of aliphatic polyurethane diacrylate, aliphatic polyurethane triacrylate, aliphatic polyurethane hexaacrylate, aliphatic polyurethane nonaacrylate or a mixture thereof.
3. The high-adhesion and high-flexibility UV coating for plastic titanium eyeglass frames according to claim 1, characterized in that: The acrylate monomer is at least one of ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, di-trimethylolpropane tetraacrylate, neopentyl glycol diacrylate, polyethylene glycol dimethacrylate, cyclotrimethylolpropane formal acrylate or a mixture thereof.
4. The high-adhesion and high-flexibility UV coating for plastic titanium eyeglass frames according to claim 1, characterized in that: The polyester acrylate is at least one of monofunctional polyester acrylate, multifunctional polyester acrylate, hyperbranched polyester acrylate, modified polyester acrylate or a mixture thereof.
5. The high-adhesion and high-flexibility UV coating for plastic titanium eyeglass frames according to claim 1, characterized in that: The initiator is at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexyl-phenyl ketone, benzophenone, and 2,4,6-trimethylbenzoyldiphenylphosphine oxide, or a mixture thereof.
6. The high-adhesion and high-flexibility UV coating for plastic titanium eyeglass frames according to claim 1, characterized in that: The leveling agent is one or a mixture of an organic silicon leveling agent, a fluorocarbon leveling agent, and a polyacrylate leveling agent.
7. The high-adhesion and high-flexibility UV coating for plastic titanium eyeglass frames according to claim 1, characterized in that: The defoamer is an organosilicon defoamer.
8. The high-adhesion and high-flexibility UV coating for plastic titanium eyeglass frames according to claim 1, characterized in that: The drier is a cobalt drier.
9. The high-adhesion and high-flexibility UV coating for plastic titanium eyeglass frames according to claim 1, characterized in that: It is made of the following raw materials in percentage by mass:
10. A method for preparing a high-adhesion and high-flexibility UV coating for a plastic titanium eyeglass frame according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Add multifunctional polyurethane acrylate and polyester acrylate into a batching tank according to mass percentage, and disperse them in a high-speed disperser; 2) adding EO3-TMPTA, CTFA, PETA and photoinitiator by weight to the mixed materials in step 1 under low-speed stirring in a high-speed disperser and dispersing; 3) Disperse the above-mentioned weight of leveling agent, defoamer, drying agent and the material mixed in step 2 in a high-speed disperser. A UV coating is obtained.
Citation Information
Patent Citations
UV / moisture dual-curing spectacle frame coating and preparation method thereof
CN109735224A
UV setting paint for plastic products
CN1175611A
Radiation curing composition for light guide fiber
CN101906235A
Radiation curing printing ink capable of being directly jetted on surface of ultraviolet curing coating and preparation method thereof
CN102558963A
High-stretch rate ultraviolet photocuring coating and coating layer
CN109535998A